Antibiotic stewardship and empirical antibiotic treatment: How can they get along?. Issue 6 (June 2017) - Zuccaro, Valentina; Columpsi, Paola; Sacchi, Paolo; Lucà, Maria Grazia; Fagiuoli, Stefano; Bruno, Raffaele
Abstract: The aim of this review is to focus on the recent knowledge on antibiotic stewardship and empiric antibiotic treatment in cirrhotic patients. The application of antimicrobial stewardship (AMS) rules appears to be the most appropriate strategy to globally manage cirrhotic patients with infectious complications: indeed they represent a unique way to provide both early diagnosis and appropriate therapy in order to avoid not only antibiotic over-prescription but, more importantly, selection and spread of antimicrobial resistance. Moreover, cirrhotic patients must be considered "frail" and susceptible to healthcare associated infections: applying AMS policies would assure a cost reduction and thus contribute to the improvement of public health strategies.